A New Precise High Flow Oxygen Therapy System Based on Sliding Mode Control Strategy. (18th April 2022) - Shi, Yan; Xu, Luyu; Xie, Fei; Cai, Maolin; Wang, Yixuan
Abstract : In recent years, precise high flow oxygen therapy as a new type of oxygen therapy machine has gradually attracted people's attention and has been widely used in hospital emergency and clinical treatment of respiratory diseases; especially in recent years, severe coronavirus disease (COVID-19) has played an important role in the treatment of patients. This paper presents a new type of precise high flow oxygen therapy machine with electromagnetic pneumatic flow valve as the core control element. A sliding mode control strategy based on the system is proposed to realize the accurate control of oxygen concentration and output flow of oxygen therapy mixture. The physical equipment of the precision high flow system is established, and its working performance is verified through the test platform. The optimization design goal of the precision high flow equipment is achieved.